A Review of Cyclic Olefin Copolymer Applications in Microfluidics and Microdevices. Issue 8 (26th April 2022) - Agha, Abdulrahman; Waheed, Waqas; Alamoodi, Nahla; Mathew, Bobby; Alnaimat, Fadi; Abu‐Nada, Eiyad; Abderrahmane, Aissa; Alazzam, Anas
Abstract: Cyclic olefin copolymers (COC) are amorphous, transparent thermoplastics composed of cyclic olefin monomers (norbornene) and linear olefins (ethene). They are increasingly utilized as fabrication materials for microsystems and microfluidic devices, owing to their promising features of low water absorption, high electrical insulation, long‐term stability of surface treatments, and resistance to a broad variety of acids and solvents. Many manufacturing processes for COC‐based devices have been developed in recent decades. These methodologies are categorized as replication methods or fast prototyping as common in fabrication of thermoplastic microfluidic devices. This review gives a full discussion of the features of COCs, the various production processes, and the numerous selected applications in microfluidic platforms. The review also explores COC's composition and fundamental features, as well as fabrication processes and applications in a variety of fields, investigates the material's potential advantages and uses, and attempts to create a comprehensive list of COC's possible benefits. Due to their unique features and simplicity of fabrication, COCs are projected to advance the future of microfluidics, microsystems, and optofluidics. Abstract : This review presents a full discussion on the properties of cyclic olefin copolymers (COC), the various fabrication processes, and numerous applications in microfluidic platforms. The review also creates a comprehensive list of COC's possible benefits and uses. Due to their unique features and fabrication simplicity, COCs are projected to advance the future of microfluidics, and microsystems.